Persistent Poverty and Employment Linkages in Türkiye: An Evalulation of the Natural Poverty Level - Güldal, Buse; Tahsin, Emine (Journal of Applied And Theoretical Social Sciences, 2025)
Introduction: This study investigates the relationship between poverty and employment in Türkiye by calculating employment elasticity and examining the changes observed in the available poverty data. Moreover, the phenomenon of "natural poverty" has been examined as a conceptual framework to assess the likelihood of poverty in Türkiye evolving into a self-sustaining condition. Method: The study is primarily based on poverty, growth and employment linkages based on elasticity calculations. Results or Findings: The study results indicate a positive relationship between economic growth and employment. However, the decrease in employment growth compared to the previous period has had an amplifying effect on persistent poverty. This change has also contributed to an increase in the rate of natural poverty. Discussion or Conclusion: This study aims to contribute to the analysis of poverty and employment linkages by conceptualising the notion of natural poverty. The existence of a persistent poverty level is conceptualised by taking into account the employment linkages. Thus, the relationship between unemployment and poverty in Turkey is evaluated within the framework of persistence.